Services commitments in preferential trade agreements: An expanded dataset - Martin Roy (World Trade Organization (WTO), 2011)
Preferential trade agreements (PTAs) on services have proliferated since 2000. This working paper briefly presents the expansion of the dataset initially developed in Marchetti and Roy (2008). The data permits to assess the extent to which market access commitments undertaken by WTO Members in PTAs go beyond GATS commitments and offers made in the context of the Doha Development Agenda. The dataset, which covers PTA commitments of 53 WTO Members (counting EU Members States as one), is available at: http://www.wto.org/english/tratop_e/serv_e/dataset_e/dataset_e.htm
Keywords: F13; F53; F59; 330; GATS; trade in services; preferential trade agreements; regionalism; GATS; Internationaler Dienstleistungsverkehr; Außenhandelspräferenz; Welt